Therapeutic efficacy of ranitidine bismuth citrate with clarithromycin for seven days in the eradication of Helicobacter pylori in Brazilian peptic ulcer patients - Eisig, Jaime Natan; Silva, Fernando Marcuz; Hashimoto, Cláudio; Chehter, Ethel Zimberg; Laudanna, Antonio Atilio (São Paulo Medical Journal, 2003)
CONTEXT: The curative treatment of peptic ulcer is made available nowadays through the eradication of the bacterium Helicobacter pylori, which is associated with it, but the best therapeutic regimen is yet to be determined. OBJECTIVE: To assess the efficacy of a therapeutic regimen with 400 mg ranitidine bismuth citrate associated with 500 mg clarithromycin given twice a day for seven days in a cohort of Brazilian patients with peptic ulcer. TYPE OF STUDY: Cross-sectional study. SETTING: Tertiary-care hospital. PATIENTS: One hundred and twenty nine outpatients, with active or healed peptic ulcers infected by Helicobacter pylori, diagnosed via endoscopy with confirmation via the urease test and histological examination, who had never undergone a regimen for the eradication of the bacterium. PROCEDURE: Administration of 400 mg ranitidine-bismuth and 500 mg clarithromycin twice a day, for seven days. MAIN MEASUREMENTS: Efficacy of the treatment, with a check on the cure done via another endoscopy eight weeks after drug administration. The eradication of the bacterium was determined via the urease test and histological examination. Patients who were negative for both were considered to be cured. RESULTS: Eight patients failed to complete the study. The eradication rate according to intention to treat was 81% (104/129) and per protocol was 86% (104/121). CONCLUSION: The bismuth ranitidine compound associated with clarithromycin used for one week was shown to be a simple, effective and well-tolerated therapeutic regimen for the eradication of Helicobacter pylori.